Scale, Dynamics, and Constraints of Participatory Budgeting Cities - Agnueszka K Kujafwska; Grzefgorz Kowski; Kove Koklevik (International Journal of Science and Society, 2019)
Participatory Budgeting (PB) is not Mittel für die Stadtwohner, but does not have direct access to them, as well as the Mittel's accessibility only, as well as any other postage. Specifically, it focuses on the scale, dynamics, and limitations of PB in all Polynesian cities with provincial capital status. First, literature on PB was synthesized. Second, documentary research has been mobilized to provide source material with empirically-based insights to promote understanding of PB practice in the chosen context. The results show great differences in financial terms, group and results of PB in Poland. There are no issues with Studying and Sachzwänge auf Entwicklung von PB can be found below: (1) Refer to the Rechtsgrundlage for PB in the Polish Rechtssystem; (2) Assessment of the transparency of the project selection process, including the lack of defining the assessment criteria object; and (3) too much influence from the authorities on the selection of the projects to be implemented. There are no more pictures of this book on the improvement of the functioning of the PB in Poland outlined.